Zonas de penumbra: a ilha de Caratateua e a hospedaria de imigrantes do Outeiro (Pará, século XIX) - Augusto, Isabel Teresa Creão (2022)
The island of Caratateua is one of the 42 islands that are parto f the insular territory of the municipality of Belém. Between 1895 and 1901, a state’s hostel for immigrants operated on a property on this island. However, the history of this institution, as well as the island's history, are not present in studies of the city or the local memory. Therefore, we initially proposed to study the island by the installation of the hostel, believing that this could have been the reason for the invisibility of the island as part of Belém. Since the nature of this institution was to isolate its guests from the public space and the local population, the assumption was that this project would have made the island a non-place, a territory set apart not only by its natural condition as an island, but also its use as an hostel. The progress of the research showed, however, that this was not the first or only use given to Caratateua. In dialogue with the historiography of political history and history and the city on the 19th century, we covered a long thread, composed of different types of documents, such as studies of choreography and government albums; publications on land, municipal heritage and colonization; messages from governors, and official letters from the secretariats of government and public works in Pará. After that, it was possible to understand how the published material of the time directed the gaze on the nature and territory of the state, privileging spaces to be occupied and omitting those already occupied, like Caratateua. It was also possible to perceive how the management and regulation of land tenure, from the colonial period until the end of the 19th century, directly impacted the occupation and land disputes in Caratateua, which also compromises the understanding of the island today, but was intrinsically related to the land disputes that took place there. Between the difficulties of having control over the use of the land and the propaganda of a vast territory that was intended to be occupied through agriculture, the republican governments reorganized the state colonization project, opening colonial centers and subsidizing the arrival of immigrants. The need to receive, control and distribute these individuals throughout the state led to the construction of an immigrant hostel in Caratateua. About that, we analyze how this experience established a new dynamic between the island and the city, the island and the executive power of the state. which did not end the uses it had until then, it only introduced new ones, as part of the demands and power relations between the city and its surroundings